2008
DOI: 10.2119/2007-00101.yu
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Expression of Receptor Tyrosine Kinases (RTKs) and IGF-I Pathway Activation in Human Uterine Leiomyomas

Abstract: Uterine leiomyomas (fibroids) are benign tumors that are prevalent in women of reproductive age. Research suggests that activated receptor tyrosine kinases (RTKs) play an important role in the enhanced proliferation observed in fibroids. In this study, a phospho-RTK array technique was used to detect RTK activity in leiomyomas compared with myometrial tissue. We found that fifteen out of seventeen RTKs evaluated in this study were highly expressed (P < 0.02-0.03) in the leiomyomas, and included the IGF-I/IGF-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 44 publications
4
89
0
3
Order By: Relevance
“…It regulates fundamental cellular functions, including transcription, translation, proliferation, growth, and survival (14,15). Recently, we, as well as other groups, presented evidence on the involvement of the PI3K/Akt signaling in leiomyoma development by demonstrating differential changes related to PI3K/Akt signaling proteins in leiomyomas compared with myometrial cells (16)(17)(18). Other investigators have shown that the PI3K/Akt pathway plays an important role in RA signaling for certain cell types, such as SH-SY5Y human neuroblastoma cells and HL-60 cells (19,20).…”
mentioning
confidence: 83%
“…It regulates fundamental cellular functions, including transcription, translation, proliferation, growth, and survival (14,15). Recently, we, as well as other groups, presented evidence on the involvement of the PI3K/Akt signaling in leiomyoma development by demonstrating differential changes related to PI3K/Akt signaling proteins in leiomyomas compared with myometrial cells (16)(17)(18). Other investigators have shown that the PI3K/Akt pathway plays an important role in RA signaling for certain cell types, such as SH-SY5Y human neuroblastoma cells and HL-60 cells (19,20).…”
mentioning
confidence: 83%
“…We proceeded to examine the activity of the p42/44 MAPK pathway (25)(26)(27), which is critical in the regulation of SMC proliferation and migration (28,29). Our results showed that leiomyoma tissues have significantly lower levels of phospho-MAPK than in myometrium tissues, but total MAPK levels were similar in both tissues (Fig.…”
mentioning
confidence: 85%
“…Recent publications from our laboratory have shown that abundant expression and activation of Akt protein can be induced in the rat uterus by administration of E 2 (1), and the expression and activation of Akt can be detected in the leiomyoma and adjacent myometrium of human uteri (2,3). The level of Akt in leiomyomatous uteri changed in parallel with the expression of estrogen (E) and P receptors, cyclin D1 and the antiapoptotic Bcl-2 protein (2)(3)(4)(5). One of the most important substrates of Akt/protein kinase B are FOXO proteins.…”
mentioning
confidence: 99%